Long‐Term Trend of the Tropical Pacific Trade Winds Under Global Warming and Its Causes. Issue 4 (14th April 2019) - Li, Yang; Chen, Quanliang; Liu, Xiaoran; Li, Jianping; Xing, Nan; Xie, Fei; Feng, Juan; Zhou, Xin; Cai, Hongke; Wang, Zhenglin
Abstract: The recent intensification of trade winds over the tropical Pacific is the strongest ever observed in the past hundred years. This strengthening trend is of great interest in recent research, but the causes are still unclear. Using two relatively long‐term surface wind data sets, the present research shows that there is an overall strengthening trend of the trades in the western equatorial Pacific and an overall weakening trend in the eastern equatorial Pacific. This long‐term trend pattern can be primarily attributed to the cold tongue mode (CTM) rather than to the impact of El Niño–Southern Oscillation (ENSO), El Niño Modoki, or Interdecadal Pacific Oscillation (IPO). The CTM, the second empirical orthogonal function mode of the sea surface temperature anomalies (SSTA) in the tropical Pacific, represents a strong long‐term trend of tropical Pacific background state under global warming. According to the Gill‐Matsuno theory, the easterly winds over the western equatorial Pacific are induced by the equatorial Pacific cooling and warming SSTA associated with the CTM, while the westerly winds over the eastern equatorial Pacific is primarily due to the eastern equatorial Pacific cooling SSTA associated with the CTM. Ultimately, an alternative explanation of past and future changes of the trades is expected to lead to improved understanding of the global climatic impacts of the enhanced trades in tropical Pacific under global warming. Key Points: There is the strengthening trend of the trades in the western equatorial Pacific and weakening trend in the eastern equatorial Pacific This long‐term trend pattern can be primarily attributed to the CTM rather than to the impact of ENSO, El Niño Modoki, or IPO Based on the Gill‐Matsuno theory, the long‐term trend of the CTM can induce the long‐term trend of trade winds